DUKUNGAN NORMATIF BAGI PEKERJA PEREMPUAN DENGAN TANGGUNG JAWAB KELUARGA: UU KETENAGAKERJAAN HINGGA UU CIPTA KERJA - Widiastiani, Nindry Sulistya (TANJUNGPURA LAW JOURNAL, 2026)
This article analyses the existence of normative support for women workers with family responsibilities in Indonesian labour law. The social structure of Indonesian society still views the function of family care as the responsibility of women. Therefore, working women are burdened with dual functions as workers and holders of care responsibilities. Both functions can lead to discrimination in the workplace for women workers. Normative support to protect these female workers is critical to note. The analysis was carried out by examining the regulations in the Manpower Act and the 2023 Job Creation Act. The analysis results show that the Acts contain several articles that provide normative support for women workers with family responsibilities, although they are not yet comprehensive and firm. First, this support is reflected in the regulations that require employers to consider the needs of workers and their families, both in employment relationships and in social security. Second, some provisions prohibit layoffs based on family responsibilities. In addition to these explicit regulations, several provisions can be implicitly interpreted as normative support for women workers with family responsibilities"”first, special regulations on reproductive health protection. Second, provisions mention the involvement of family or heirs in employment rights. Third, the recognition of significant events involving workers"™ families. However, existing regulations are still inadequate in providing comprehensive normative support for women workers with family responsibilities. Indonesia should immediately ratify the International Labour Organization Convention Number 156 to strengthen such protection.